An organic modified ion sieve composite adsorption material and its preparation method and application

The preparation process of manganese-based ion sieve adsorbent is improved through step-by-step synthesis method, and the problems of poor resistance to organic solvents and reduced adsorption amount in the prior art are solved, thereby achieving a more efficient lithium ion adsorption effect.

CN119075953BActive Publication Date: 2025-02-11INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411587494.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In the prior art, when preparing manganese-based ion sieve adsorbents, there are problems such as poor resistance to organic solvents and a decrease in adsorption amount under neutral conditions.

Method used

The step-by-step synthesis method is adopted to improve the cross-linking degree and organic solvent resistance of the adsorbent material through the prepolymerization-swelling-crosslinking-organic modification method, and the surface charge density of the adsorbent is improved by introducing a negative charge functional base.

Benefits of technology

The adsorption amount of adsorbent materials under neutral conditions is significantly improved, the tolerance to organic solvents is enhanced, and the pH sensitivity is reduced, and the adsorption amount is increased by more than 2 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application discloses an organic modified ion sieve composite adsorbent material and its preparation method and application. The preparation method comprises the following steps: (1) dissolving a polymerization monomer and an initiator in a first organic solvent to obtain an oil phase, mixing and stirring with an ion sieve powder to obtain a prepolymer, and then adding the prepolymer into an aqueous phase for dispersion to obtain an ion sieve gel; (2) adding an initiator and a cross-linking agent to the ion sieve gel, and performing a suspension polymerization reaction to obtain a granular ion sieve; (3) dissolving the granular ion sieve in a second organic solvent, adding a Lewis acid catalyst and a negatively charged functional group, and washing the reaction product with a weak acid, washing with water, and drying to obtain a composite adsorbent material. The present application adopts a prepolymerization-swelling-cross-linking-organic modification method, and the composite adsorbent material obtained by step-by-step polymerization has good organic solvent tolerance; the introduction of negatively charged functional groups can increase the surface charge density of the adsorbent, and the pH sensitivity of the product is significantly reduced, and the adsorption amount is increased by more than 2 times compared with that before modification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of resin materials, and in particular to an organic modified ion sieve composite adsorption material and a preparation method and application thereof. Background Art

[0002] With the transformation of energy structure and the development of electric vehicle industry, the strategic position of lithium resources has become increasingly prominent. Salt lake brine is one of the main sources of lithium resources. Manganese ion sieve has a cubic crystal structure and has a specific adsorption capacity for lithium ions after acid activation, which can be used to extract lithium from salt lake brine.

[0003] The existing technology adopts the method of dissolving the polymerization monomer in an organic solvent, then mixing it with the manganese ion sieve powder for prepolymerization, and then adding water phase to directly carry out suspension polymerization to prepare the manganese ion sieve adsorbent. The manganese ion sieve prepared in this way has the problems of poor organic solvent tolerance and serious reduction of adsorption capacity under neutral conditions.

[0004] Therefore, developing a lithium adsorption material that is tolerant to organic solvents and has low pH sensitivity during water treatment is an urgent problem to be solved in the art. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present application provides an organic modified ion sieve composite adsorption material and a preparation method thereof. Through a step-by-step synthesis method, the cross-linking degree of the adsorption material product is improved, the organic solvent tolerance of the adsorption material product is improved, and the adsorption amount of the adsorption material product under neutral conditions is increased. It is used as an adsorbent for lithium extraction from salt lake brine and has excellent adsorption performance.

[0006] In a first aspect, the present application provides a method for preparing an organic modified ion sieve composite adsorbent material, the preparation method comprising the following steps:

[0007] (1) dissolving a polymerization monomer and an initiator in a first organic solvent to obtain an oil phase, mixing the oil phase with an ion sieve powder, and performing a prepolymerization reaction and slurrying to obtain a prepolymer, and adding an aqueous phase to the prepolymer for dispersion at room temperature to obtain an ion sieve gel; the mass of the first organic solvent is 20% to 100% of the mass of the polymerization monomer;

[0008] (2) dissolving the initiator in the cross-linking agent, and then adding the above-mentioned ion sieve gel, and heating it to carry out suspension polymerization after swelling to obtain a granular ion sieve; the suspension polymerization reaction temperature is 78°C to 90°C;

[0009] (3) Under nitrogen protection, the granular ion sieve is dissolved in a second organic solvent, and a Lewis acid catalyst and a negatively charged functional group are added to carry out an organic reaction. The reaction product is washed with weak acid, washed with water, and dried to obtain a composite adsorption material.

[0010] Based on the above embodiments, the present application adopts the method of prepolymerization-swelling-crosslinking-organic modification, and the composite adsorbent material obtained by step-by-step polymerization is not easy to fall off during repeated use, the granular ion sieve does not dissolve during the modification process, and has good tolerance to organic solvents; at the same time, the negatively charged functional groups introduced by the negatively charged functional groups can effectively increase the surface charge density of the adsorbent, especially to make up for the insufficient adsorption driving force under neutral conditions, and the pH sensitivity is significantly reduced. Compared with before modification, the adsorption amount is increased by more than 2 times. By using the initiator separately, the polymerization reaction can be made more uniform and the polymerization effect can be improved. By dissolving the initiator in the crosslinker and then dissolving the ion sieve gel, the initiator and the crosslinker can be diffused into the ion sieve gel at a synchronized speed, thereby improving product performance.

[0011] In some embodiments, the polymerizable monomer includes a monoolefin monomer, and the monoolefin monomer includes at least one of styrene, a styrene-modified monomer, or a methacrylate monomer. The styrene-modified monomer includes chloromethylstyrene and aminostyrene, and the methacrylate monomer includes methyl methacrylate and ethylene glycol methacrylate. For example, the polymerizable monomer may be at least one of styrene, chloromethylstyrene, aminostyrene, methyl methacrylate, or ethylene glycol methacrylate.

[0012] In some embodiments, the initiator is an oil-soluble initiator, which includes at least one of benzoyl peroxide or azobisisobutyronitrile. Wherein, the mass of the initiator in step (1) is 0.5% to 3% of the mass of the polymerized monomer. For example, the mass of the initiator in step (1) can be 0.5%, 1.0%, 1.1%, 1.6%, 2.2%, 2.8%, 3% of the mass of the polymerized monomer, or a value in the range of any two of these values. The mass of the initiator in step (2) is 0.5% to 3% of the mass of the crosslinker. For example, the mass of the initiator in step (2) can be 0.5%, 0.8%, 1.4%, 1.7%, 2.4%, 2.8%, 3% of the mass of the crosslinker, or a value in the range of any two of these values.

[0013] In some embodiments, the first organic solvent comprises at least one of ethyl acetate, n-octanol or ethylbenzene. The mass of the first organic solvent is 20% to 100% of the mass of the polymerized monomer. For example, the mass of the first organic solvent can be 20%, 35%, 54%, 70%, 88%, 100% of the mass of the polymerized monomer, or a value in the range of any two of these values.

[0014] In some embodiments, the oil phase further comprises a porogen, which is an oil-soluble inert substance, and comprises at least one of liquid wax, petroleum ether or white oil. The mass of the porogen is 50% to 200% of the mass of the polymerized monomer. For example, the mass of the porogen can be 50%, 63%, 107%, 121%, 156%, 192%, 200% of the mass of the polymerized monomer, or a value within the range consisting of any two of these values.

[0015] In some embodiments, the ion sieve powder comprises a manganese ion sieve. The particle size of the ion sieve powder is D μm, 0.1≤D≤1. For example, the particle size of the ion sieve powder can be 0.1μm, 0.2μm, 0.3μm, 0.5μm, 0.7μm, 0.9μm, 1μm, or a value in the range of any two of these values. The mass of the ion sieve powder is 5% to 80% of the mass of the polymerized monomer. For example, the mass of the ion sieve powder can be 5%, 8%, 34%, 38%, 56%, 74%, 80% of the mass of the polymerized monomer, or a value in the range of any two of these values.

[0016] In some embodiments, the aqueous phase further comprises a polymer dispersant, and the polymer dispersant comprises polyvinyl alcohol. Based on the mass of the aqueous phase, the mass proportion of the polymer dispersant is 0.5% to 3%. For example, based on the mass of the aqueous phase, the mass proportion of the polymer dispersant can be 0.5%, 1.0%, 1.1%, 1.6%, 2.4%, 2.7%, 3%, or a value within the range of any two of these values.

[0017] In some embodiments, the aqueous phase further comprises an inorganic salt, and the inorganic salt comprises sodium chloride. Based on the mass of the aqueous phase, the mass proportion of the inorganic salt is 2% to 10%. For example, based on the mass of the aqueous phase, the mass proportion of the inorganic salt can be 2%, 3%, 5%, 6%, 8%, 9%, 10%, or a value within the range composed of any two of these values.

[0018] In some embodiments, the volume ratio of the oil phase to the water phase is 1:(3-8). For example, the volume ratio of the oil phase to the water phase can be 1:3, 1:3.5, 1:4.8, 1:5.2, 1:7.6, 1:8, or a value within the range formed by any two of these values.

[0019] In some embodiments, the crosslinking agent includes a diene monomer, specifically at least one of divinylbenzene and ethylene glycol dimethacrylate. The mass ratio of the crosslinking agent to the ion sieve gel is 0.1 to 1. For example, the mass ratio of the crosslinking agent to the ion sieve gel can be 0.1, 0.3, 0.4, 0.6, 0.7, 0.8, 1, or a value in the range of any two of these values.

[0020] In some embodiments, the second organic solvent comprises at least one of dichloromethane and dichloroethane. The mass of the second organic solvent is 30 to 80 times the mass of the granular ion sieve. For example, the mass of the second organic solvent can be 30 times, 31.4 times, 43.4 times, 59.6 times, 61.2 times, 74.2 times, 80 times the mass of the granular ion sieve, or a value within the range consisting of any two of these values.

[0021] In some embodiments, the Lewis acid catalyst includes one of anhydrous zinc chloride, anhydrous aluminum chloride, or anhydrous ferric chloride; the mass ratio of the Lewis acid catalyst to the granular ion sieve is 1:(0.8-2.5). For example, the mass ratio of the Lewis acid catalyst to the granular ion sieve can be 1:0.8, 1:1.2, 1:1.8, 1:2.1, 1:2.5, or a value within the range of any two of these values.

[0022] In some embodiments, the negatively charged functional group is an organic substance that can undergo a substitution reaction with side benzene or chlorine, including at least one of aminoacetic acid, iminodiacetic acid, sulfonic acid or chloroacetic acid. The mass of the negatively charged functional group is 1% to 5% of the mass of the granular ion sieve. For example, the mass of the negatively charged functional group can be 1%, 1.4%, 2.4%, 2.6%, 4.1%, 4.2%, 5% of the mass of the granular ion sieve, or a value within the range composed of any two of these values.

[0023] In some embodiments, the reaction temperature of the prepolymerization reaction in step (1) is 65°C to 80°C, and the reaction time of the prepolymerization reaction is 30min to 90min. For example, the reaction temperature of the prepolymerization reaction can be 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, or a value in the range of any two of these values. For example, the reaction time of the prepolymerization reaction can be 30min, 35min, 40min, 45min, 50min, 55min, 60min, 65min, 70min, 75min, 80min, 85min, 90min, or a value in the range of any two of these values.

[0024] In some embodiments, the temperature of the room temperature dispersion in step (1) is 30°C to 50°C, and the dispersion time of the room temperature dispersion is 10 min to 60 min. For example, the dispersion time of the room temperature dispersion can be 10 min, 19 min, 25 min, 32 min, 45 min, 51 min, 60 min, or a value within the range formed by any two of these values.

[0025] In some embodiments, the mixing and stirring in step (1) is electromagnetic stirring, and the stirring speed is 200 r / min to 600 r / min. For example, the stirring speed of the mixing and stirring can be 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, or a value within the range formed by any two of these values.

[0026] In some embodiments, the swelling time in step (2) is 2 h to 5 h. For example, the swelling time in step (2) can be 2 h, 2.5 h, 2.6 h, 3.6 h, 3.9 h, 4.4 h, 5 h, or a value in the range of any two of these values.

[0027] In some embodiments, the suspension polymerization reaction time in step (2) is 4 hours to 8 hours. For example, the suspension polymerization reaction time can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 7 hours, 8 hours, or a value in the range of any two of these values. The suspension polymerization reaction temperature is 78°C to 90°C. For example, the suspension polymerization reaction temperature can be 78°C, 80°C, 82°C, 85°C, 87°C, 88°C, 90°C, or a value in the range of any two of these values.

[0028] In some embodiments, in step (3): the reaction temperature of the organic reaction is 25°C to 60°C. For example, the reaction temperature of the organic reaction can be 25°C, 26°C, 38°C, 44°C, 53°C, 58°C, 60°C, or a value within the range of any two of these values. The reaction time is 12h to 24h. For example, the reaction time of the organic reaction can be 12h, 13h, 15h, 16h, 19h, 21h, 24h, or a value within the range of any two of these values. The weak acid is hydrochloric acid, and the pH of the hydrochloric acid is 1 to 2; the drying is vacuum drying, and the drying temperature is 60°C.

[0029] In a second aspect, the present application provides an organic modified ion sieve composite adsorption material, which is prepared by the above-mentioned preparation method.

[0030] In a third aspect, the present application provides the use of the above-mentioned organic modified ion sieve composite adsorption material as a lithium adsorbent in the extraction of lithium from raw brine in salt lakes.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The organic modified ion sieve composite adsorbent material and preparation method thereof provided in the present application are obtained by step-by-step polymerization through a prepolymerization-swelling-crosslinking-organic modification method. The composite adsorbent material is not easy to fall off during repeated use, the granular ion sieve does not dissolve during the modification process, and has good tolerance to organic solvents. At the same time, the negatively charged functional groups introduced through the negatively charged functional groups can effectively increase the surface charge density of the adsorbent and improve product performance, especially make up for the insufficient driving force for adsorption under neutral conditions, significantly reduce pH sensitivity, and increase the adsorption amount by more than 2 times compared with before modification.

[0033] The organic modified ion sieve composite adsorption material provided in the present application is a composite adsorbent with organic-inorganic synergistic adsorption performance. The saturated adsorption capacity when directly used in salt lake raw brine with pH=6.8 is 15.3mg / g~19.3mg / g, the adsorption equilibrium time is 2h~4h, the saturated adsorption capacity after 10 cycles is 13.8mg / g~18.1mg / g, the saturated adsorption equilibrium time after 10 cycles is 2h~4h, and the adsorption capacity is maintained above 95% after 10 cycles. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0035] Example

[0036] The following examples and comparative examples are given to more specifically illustrate the embodiments of the present application. It will be appreciated by those skilled in the art that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "part" and "%" are mass references.

[0037] The experimental materials used in the embodiments and comparative examples of the present invention are as follows:

[0038] Manganese ion sieve preparation method:

[0039] Lithium carbonate and manganese carbonate were mixed at a molar ratio of Li / Mn = 0.8, calcined in a muffle furnace at 543 K for 2 hours, and then calcined at 673 K for 6 hours. After cooling, 0.25 mol / L HCl was added and reacted at 323 K for 24 hours to obtain a manganese-based ion sieve.

[0040] Example 1

[0041] This embodiment provides a method for preparing an organic modified ion sieve composite adsorption material, and the specific preparation method includes the following steps:

[0042] (1) Dissolve 5 g of sodium chloride and 1 g of polyvinyl alcohol in 100 mL of water, stir in a 250 mL three-necked flask, and heat to 40°C to obtain an aqueous phase;

[0043] (2) Weigh 10 g of styrene, 0.1 g of benzoyl peroxide, 10 g of ethyl acetate, and 10 g of liquid wax respectively, and mix them evenly to obtain an oil phase;

[0044] (3) Add 5 g of manganese ion sieve, heat in a water bath to 78 °C under electromagnetic stirring at 500 r / min, react for 90 min to obtain a prepolymer, add the prepolymer to the water phase, adjust the stirring speed to 200 r / min, and obtain a sol with a particle size of about 500 μm;

[0045] (4) Dissolve 0.05 g of benzoyl peroxide in 5 g of divinylbenzene, add the sol to swell for 5 hours, heat to 78 ° C and react for 8 hours to obtain a highly cross-linked ion sieve adsorbent;

[0046] (5) Weigh 1 g of the product and place it in 30 mL of dichloromethane. Allow to swell for 3 hours. Add 1 g of iminodiacetic acid and 1 g of anhydrous zinc chloride. React at 30 °C for 12 hours and filter out.

[0047] (6) The mixture was washed with hydrochloric acid having a pH value of 1 until the washing liquid was colorless, and excess water was washed with ethanol. After vacuum drying for 6 hours, a composite adsorbent was obtained, which was sieved with 450 μm and 550 μm gauze to obtain the final product.

[0048] Example 2

[0049] This embodiment provides a method for preparing an organic modified ion sieve composite adsorbent material, which is different from that of embodiment 1 in that the preparation parameters are different. The specific preparation method includes the following steps:

[0050] (1) Dissolve 5 g of sodium chloride and 2 g of polyvinyl alcohol in 200 mL of water, stir in a 500 mL three-necked flask, and heat to 40°C to obtain an aqueous phase;

[0051] (2) Weigh 15 g of styrene, 0.2 g of benzoyl peroxide, and 15 g of butyl acetate respectively, and mix them evenly to obtain an oil phase;

[0052] (3) Add 15 g of manganese ion sieve, heat in a water bath to 78 °C under electromagnetic stirring at 500 r / min, react for 70 min to obtain a prepolymer, add the prepolymer to the water phase, adjust the stirring speed to 300 r / min, and obtain a sol with a particle size of about 400 μm;

[0053] (4) Dissolve 0.03 g of benzoyl peroxide in 3 g of divinylbenzene, add the sol to swell for 6 hours, heat to 78 °C and react for 7 hours to obtain a highly cross-linked ion sieve adsorbent;

[0054] (5) Weigh 1 g of the product and place it in 40 mL of dichloroethane. Allow to swell for 3 hours. Add 0.2 g of iminodiacetic acid and 1 g of anhydrous aluminum chloride. React at 50 °C for 12 hours and filter out.

[0055] (6) The mixture was washed with hydrochloric acid having a pH value of 1 until the washing liquid was colorless, and excess water was washed with ethanol. After vacuum drying for 6 hours, a composite adsorbent was obtained, which was sieved with 350 μm and 450 μm gauze to obtain the final product.

[0056] Example 3

[0057] This embodiment provides a method for preparing an organic modified ion sieve composite adsorbent material, which is different from that of embodiment 1 in that the preparation parameters are different. The specific preparation method includes the following steps:

[0058] (1) Dissolve 5 g of sodium chloride and 2 g of polyvinyl alcohol in 200 mL of water, stir in a 500 mL three-necked flask, and heat to 40°C to obtain an aqueous phase;

[0059] (2) Weigh 15 g of chlorostyrene, 0.2 g of benzoyl peroxide, and 15 g of butyl acetate respectively, and mix them evenly to obtain an oil phase;

[0060] (3) Add 15 g of manganese ion sieve, heat in a water bath to 78 °C under electromagnetic stirring at 400 r / min, react for 70 min to obtain a prepolymer, add the prepolymer to the water phase, adjust the stirring speed to 350 r / min, and obtain a sol with a particle size of about 400 μm;

[0061] (4) Dissolve 0.1 g of benzoyl peroxide in 10 g of divinylbenzene, add the sol to swell for 6 hours, heat to 78 °C and react for 8 hours to obtain a highly cross-linked ion sieve adsorbent;

[0062] (5) Weigh 1 g of the product and place it in 40 mL of dichloromethane. Allow it to swell for 5 hours. Add 0.1 g of chloroacetic acid and 2 g of anhydrous aluminum chloride. React at 30 °C for 18 hours and filter out.

[0063] (6) The mixture was washed with hydrochloric acid having a pH value of 1 until the washing liquid was colorless, and excess water was washed with ethanol. After vacuum drying for 6 hours, a composite adsorbent was obtained, which was sieved with 450 μm and 550 μm gauze to obtain the final product.

[0064] Example 4

[0065] This embodiment provides a method for preparing an organic modified ion sieve composite adsorbent material, which is different from that of embodiment 1 in that the preparation parameters are different. The specific preparation method includes the following steps:

[0066] (1) Dissolve 4 g of sodium chloride and 2 g of polyvinyl alcohol in 200 mL of water, stir in a 500 mL three-necked flask, and heat to 40°C to obtain an aqueous phase;

[0067] (2) Weigh 10 g of methyl methacrylate, 0.1 g of azobisisobutyronitrile, 10 g of butyl acetate, and 5 g of petroleum ether respectively, and mix them evenly to obtain an oil phase;

[0068] (3) Add 10 g of manganese ion sieve, heat to 80 ° C in a water bath under electromagnetic stirring at 500 r / min, react for 80 min to obtain a prepolymer, add the prepolymer to the water phase, adjust the stirring speed to 500 r / min, and obtain a sol with a particle size of about 200 μm;

[0069] (4) Dissolve 0.05 g of azobisisobutyronitrile in 5 g of ethylene glycol dimethacrylate, add the sol to swell for 6 hours, heat to 85°C and react for 8 hours to obtain a highly cross-linked ion sieve adsorbent;

[0070] (5) Weigh 1 g of the product and place it in 30 mL of dichloromethane. Allow to swell for 6 hours. Add 0.8 g of chloroacetic acid and 2 g of anhydrous ferric chloride. React at 30 °C for 18 hours and filter out.

[0071] (6) The mixture was washed with hydrochloric acid having a pH value of 1 until the washing liquid was colorless, and excess water was washed with ethanol. After vacuum drying for 6 hours, a composite adsorbent was obtained, which was sieved with 350 μm and 450 μm gauze to obtain the final product.

[0072] Example 5

[0073] This embodiment provides a method for preparing an ion sieve adsorbent material, which differs from Embodiment 1 in that the preparation parameters are different. The specific preparation method includes the following steps:

[0074] (1) Dissolve 5 g of sodium chloride and 1 g of polyvinyl alcohol in 100 mL of water, stir in a 250 mL three-necked flask, and heat to 78 °C to obtain an aqueous phase;

[0075] (2) Weigh 10 g of styrene, 0.12 g of benzoyl peroxide, and 20 g of ethyl acetate respectively, and mix them evenly to obtain an oil phase;

[0076] (3) Add 6 g of manganese ion sieve, heat in a water bath to 78 °C under electromagnetic stirring at 500 r / min, react for 90 min to obtain a prepolymer, add the prepolymer to the water phase, adjust the stirring speed to 200 r / min, and obtain a sol with a particle size of about 500 μm;

[0077] (4) 0.05 g of benzoyl peroxide was dissolved in 5 g of divinylbenzene, added to the sol and swelled for 5 hours, and then heated to 78°C for reaction for 8 hours. Only a random polymer with a poor spherical shape was obtained. The amount of organic solvent used exceeded the preferred range, and the polymer swelled excessively after molding and could not be solidified into spheres.

[0078] (5) Weigh 1 g of random polymer into 30 mL of dichloromethane and allow to swell for 6 hours. Add 0.8 g of chloroacetic acid and 2 g of anhydrous ferric chloride, react at 30 °C for 18 hours, and filter out.

[0079] (6) The mixture was washed with hydrochloric acid at a pH of 1 until the washing solution became colorless, and then the excess water was washed with ethanol. After vacuum drying for 6 hours, an irregular block-shaped adsorption material was obtained.

[0080] Example 6

[0081] This embodiment provides a method for preparing an ion sieve adsorbent material, which differs from Embodiment 1 in that the preparation parameters are different. The specific preparation method includes the following steps:

[0082] (1) Dissolve 5 g of sodium chloride and 1 g of polyvinyl alcohol in 100 mL of water, stir in a 250 mL three-necked flask, and heat to 78 °C to obtain an aqueous phase;

[0083] (2) Weigh 10 g of styrene, 2 g of divinylbenzene, 0.12 g of benzoyl peroxide, 10 g of ethyl acetate, and 10 g of liquid wax respectively, and mix them evenly to obtain an oil phase;

[0084] (3) Add 6 g of manganese ion sieve, heat in a water bath to 78 °C under electromagnetic stirring at 500 r / min, react for 90 min to obtain a prepolymer, add the prepolymer to the water phase, adjust the stirring speed to 200 r / min, and obtain a sol with a particle size of about 500 μm;

[0085] (4) 0.05 g of benzoyl peroxide was dissolved in 5 g of divinylbenzene, added to the sol and swelled for 5 hours, and then heated to 95°C for reaction for 8 hours to obtain a ribbon-shaped hard polymer. The reaction temperature of the suspension polymerization reaction exceeded the preferred range, and the polymer underwent a viscous-flow state transition at high temperature, resulting in severe adhesion under stirring.

[0086] (5) Weigh 1 g of the crushed polymer and place it in 40 mL of dichloroethane. Allow it to swell for 3 hours. Add 0.2 g of iminodiacetic acid and 1 g of anhydrous aluminum chloride. React at 50 °C for 12 hours and filter out.

[0087] (6) The mixture was washed with hydrochloric acid at a pH of 1 until the washing solution became colorless, and then the excess water was washed with ethanol. After vacuum drying for 6 hours, an irregular block-shaped adsorbent was obtained.

[0088] Comparative Example 1

[0089] This comparative example provides a method for preparing an ion sieve adsorbent material, which is different from Example 1 in that slurrying and prepolymerization are performed separately. The specific preparation method includes the following steps:

[0090] (1) Dissolve 5 g of sodium chloride and 1 g of polyvinyl alcohol in 100 mL of water, stir in a 250 mL three-necked flask, and heat to 85°C to obtain an aqueous phase;

[0091] (2) Weigh 10 g of styrene, 2 g of divinylbenzene, 0.12 g of benzoyl peroxide, 10 g of ethyl acetate, and 10 g of liquid wax respectively, and mix them evenly to obtain an oil phase;

[0092] (3) Add 6 g of manganese ion sieve, slurry for 1 hour under electromagnetic stirring at 500 r / min, then heat to 78°C in a water bath and react for 90 min to obtain a prepolymer. Add the prepolymer to the water phase and adjust the stirring speed to 200 r / min to obtain a sol with a particle size of about 500 μm.

[0093] (4) Dissolve 0.05 g of benzoyl peroxide in 5 g of divinylbenzene, add the sol to swell for 5 hours, heat to 78 ° C and react for 8 hours to obtain an ion sieve adsorbent;

[0094] (5) Weigh 1 g of the product and place it in 30 mL of dichloromethane. Allow to swell for 3 hours. Add 1 g of iminodiacetic acid and 1 g of anhydrous zinc chloride. React at 30 °C for 12 hours and filter out.

[0095] (6) The mixture was washed with hydrochloric acid having a pH value of 1 until the washing liquid was colorless, and excess water was washed with ethanol. After vacuum drying for 6 hours, an adsorbent was obtained, which was sieved with 450 μm and 550 μm gauze to obtain the final product.

[0096] Comparative Example 2

[0097] This comparative example is a method for preparing an ion sieve adsorbent material, which is different from Example 1 in that there is no prepolymerization, and slurrying and suspension polymerization are carried out simultaneously. The specific preparation method includes the following steps:

[0098] (1) Dissolve 5 g of sodium chloride and 1 g of polyvinyl alcohol in 100 mL of water, stir in a 250 mL three-necked flask, and heat to 85°C to obtain an aqueous phase;

[0099] (2) Weigh 10 g of styrene, 2 g of divinylbenzene, 0.12 g of benzoyl peroxide, 10 g of ethyl acetate, and 10 g of liquid wax respectively, and mix them evenly to obtain an oil phase;

[0100] (3) Add 6 g of manganese ion sieve into the water phase and adjust the stirring speed to 200 r / min to obtain a sol with a particle size of about 500 μm;

[0101] (4) Dissolve 0.05 g of benzoyl peroxide in 5 g of divinylbenzene, add the sol to swell for 5 hours, heat to 78 ° C and react for 8 hours to obtain an ion sieve adsorbent;

[0102] (5) Weigh 1 g of the product and place it in 30 mL of dichloromethane. Allow to swell for 3 hours. Add 1 g of iminodiacetic acid and 1 g of anhydrous zinc chloride. React at 30 °C for 12 hours and filter out.

[0103] (6) The mixture was washed with hydrochloric acid having a pH value of 1 until the washing liquid was colorless, and excess water was washed with ethanol. After vacuum drying for 6 hours, an adsorbent was obtained, which was sieved with 450 μm and 550 μm gauze to obtain the final product.

[0104] Comparative Example 3

[0105] The method for preparing an ion sieve adsorbent material in this comparative example is different from that in Example 1 in that no organic modification step is performed. The specific preparation method includes the following steps:

[0106] (1) Dissolve 5 g of sodium chloride and 1 g of polyvinyl alcohol in 100 mL of water, stir in a 250 mL three-necked flask, and heat to 78 °C to obtain an aqueous phase;

[0107] (2) Weigh 10 g of styrene, 0.12 g of benzoyl peroxide, 10 g of ethyl acetate, and 10 g of liquid wax respectively, and mix them evenly to obtain an oil phase;

[0108] (3) Add 6 g of manganese ion sieve, heat to 78 °C in a water bath under electromagnetic stirring at 500 r / min, react for 90 min to obtain a prepolymer, add the prepolymer to the aqueous phase, adjust the stirring speed to 200 r / min, obtain a sol with a particle size of about 500 μm, swell the sol for 5 hours, heat to 78 °C and react for 8 hours to obtain an ion sieve adsorbent.

[0109] The performance of the granular ion sieves provided in Examples 1 to 6 and Comparative Examples 1 to 3 was tested, and the specific method is as follows:

[0110] (1) Particle size: Use a laser particle size analyzer to measure. Add a certain amount of granular ion sieve into water and stir it. Measure its refractive index to determine the particle size.

[0111] (2) Water content: Use a moisture meter to measure. Select about 1g of granular ion sieve and place it in the moisture meter. Select the 160℃ 3-minute program for rapid measurement;

[0112] (3) Balling rate: The product is weighed after screening, and the moisture content is measured to determine its dry weight m. The total mass of the polymerized monomer and ion sieve powder during feeding is m0, and m0 / m is the balling rate.

[0113] (4) Saturated adsorption capacity: Lithium hydroxide solutions with concentrations of 0.5 g / L, 1 g / L, 1.5 g / L, and 2 g / L were selected as simulated solutions. A granular ion sieve with a dry weight of m was placed in a conical flask, and a simulated solution with a volume of V was added. Static adsorption was performed in a constant temperature shaker. The adsorbed solution and the initial simulated solution were measured using ICP to determine the lithium concentrations c and c0, respectively. The saturated adsorption capacity was (c-c0)*V / m;

[0114] (5) Adsorption equilibrium time: Prepare a certain amount of 500 ppm lithium hydroxide solution, put it into a granular ion sieve, and perform static adsorption in a constant temperature shaker. Take samples every half an hour and use ICP to measure the lithium concentration until the lithium concentration no longer changes. The time taken is the adsorption equilibrium time.

[0115] Table 1

[0116]

[0117] From the data in Table 1, it can be seen that the organic modified ion sieve composite adsorption materials synthesized by the method provided by the present invention in Examples 1-4 are black, non-adhesive spherical, with controllable particle size (350-550 μm), water content greater than 55%, and ball formation rate greater than 70% after screening, compared with Comparative Examples 1-3.

[0118] Table 2

[0119]

[0120] From the data in Table 2, it can be seen that the saturated adsorption capacity of the ion sieve adsorbent material synthesized in Examples 1-6 is higher than that of Comparative Examples 1-3. The adsorption equilibrium time of the ion sieve adsorbent material synthesized in Examples 1-4 is shorter, and the saturated adsorption capacity after 10 repetitions is also significantly improved compared with Comparative Examples 1-3.

[0121] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing an organic modified ion sieve composite adsorbent material, characterized in that: The preparation method comprises the following steps: (1) dissolving a polymerization monomer and an initiator in a first organic solvent to obtain an oil phase, mixing the oil phase with an ion sieve powder, and performing a prepolymerization reaction and slurrying to obtain a prepolymer, and adding an aqueous phase to the prepolymer for dispersion at room temperature to obtain an ion sieve gel; the mass of the first organic solvent is 20% to 100% of the mass of the polymerization monomer; (2) dissolving an initiator in a cross-linking agent, and then adding the ion sieve gel, swelling it, and then heating it to carry out a suspension polymerization reaction to obtain a granular ion sieve; the suspension polymerization reaction temperature is 78°C to 90°C; (3) Under nitrogen protection, the granular ion sieve is dissolved in a second organic solvent, and a Lewis acid catalyst and a negatively charged functional group are added to carry out an organic reaction, and the reaction product is washed with weak acid, washed with water, and dried to obtain a composite adsorption material.

2. The preparation method according to claim 1, characterized in that: The polymerizable monomer includes at least one of styrene, chloromethylstyrene, aminostyrene, methyl methacrylate or ethylene glycol methacrylate.

3. The preparation method according to claim 1, characterized in that: The initiator comprises at least one of benzoyl peroxide and azobisisobutyronitrile; wherein the mass of the initiator in step (1) is 0.5% to 3% of the mass of the polymerization monomer; and the mass of the initiator in step (2) is 0.5% to 3% of the mass of the crosslinking agent; The cross-linking agent includes at least one of divinylbenzene and ethylene glycol dimethacrylate; the mass ratio of the cross-linking agent to the ion sieve gel is 0.1-1.

4. The preparation method according to claim 1, characterized in that: The first organic solvent comprises at least one of ethyl acetate, n-octanol or ethylbenzene; and / or, The second organic solvent includes at least one of dichloromethane and dichloroethane, and the mass of the second organic solvent is 30 to 80 times the mass of the granular ion sieve.

5. The preparation method according to claim 1, characterized in that: The ion sieve powder includes a manganese-based ion sieve; The particle size of the ion sieve powder is D μm, 0.1≤D≤1; The mass of the ion sieve powder is 5% to 80% of the mass of the polymerized monomer.

6. The preparation method according to claim 1, characterized in that: The Lewis acid catalyst includes one of anhydrous zinc chloride, anhydrous aluminum chloride or anhydrous ferric chloride; The mass ratio of the Lewis acid catalyst to the granular ion sieve is 1:0.8-2.

5.

7. The preparation method according to claim 1, characterized in that: The negatively charged functional group comprises at least one of aminoacetic acid, iminodiacetic acid, sulfonic acid or chloroacetic acid; The mass of the negatively charged functional group is 1% to 5% of the mass of the granular ion sieve.

8. The preparation method according to claim 1, characterized in that: In step (3): The reaction temperature of the organic reaction is 25°C to 60°C, and the reaction time is 12h to 24h; The weak acid is hydrochloric acid, and the pH of the hydrochloric acid is 1-2; The drying is vacuum drying, and the drying temperature is 60°C.

9. An organic modified ion sieve composite adsorption material, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the organic modified ion sieve composite adsorption material according to claim 9 as a lithium adsorbent in extracting lithium from raw brine in salt lakes.

Citation Information

Patent Citations

  • Method for preparing spherical granular lithium ion sieve

    CN106084102A

  • Ion sieve for selectively extracting lithium as well as preparation method and application of ion sieve

    CN117065731A